Thickness of the nasolacrimal duct and the adjacent maxillary bone in different skeletal patterns using MSCT: A retrospective study - Marcelo Oldack Silva dos Santos; Daniel Adrian Silva Souza; Maria Clara Albuquerque Borges; Iêda Margarida Crusoé Rocha Rebello; Frederico Sampaio Neves; Sandra de Cássia Santana Sardinha (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
Objectives: To evaluate the anatomy of the nasolacrimal duct and the adjacent maxillary bone thickness using multislice computed tomography. Methods: Tomographic images of 92 individuals (184 sides) were analyzed according to sex, side, and sagittal (Class I, II, and III) and vertical (mesocephalic, brachycephalic, and dolichocephalic) skeletal patterns. The largest diameters of the nasolacrimal duct and the thickness of the adjacent maxillary bone were measured when the lacrimomaxillary suture was completely visible. In addition, the measurements were performed 2 mm above and below the midpoint. The maxillary bone and nasolacrimal duct measurements were analyzed by one-way ANOVA with Tukey's post-hoc test. Results: Females had a significantly narrower lacrimal duct at the midpoint (p=0.026) and 2 mm above it (p=0.025). Maxillary bone thickness was greater in Class II individuals compared to Class I at the midpoint (p=0.012) and 2 mm above it (p=0.027). The dolichocephalic group had greater maxillary bone thickness at the midpoint (p=0.014) and 2 mm below it (p=0.005) compared to the brachycephalic group. Maxillary bone thickness was greater in mesocephalic individuals compared to dolichocephalic individuals (p=0.04). Conclusions: Brachycephalic Class I individuals have lower maxillary bone thickness adjacent to the nasolacrimal duct, which increases the risk of injury during the bone fixation process.